Adjuvant 131I-metuximab for hepatocellular carcinoma after liver resection: a randomised, controlled, multicentre, open-label, phase 2 trial. (June 2020) - Li, Jun; Xing, Jingliang; Yang, Yefa; Liu, Jingfeng; Wang, Wentao; Xia, Yong; Yan, Zhenlin; Wang, Kui; Wu, Dong; Wu, Lu; Wan, Xuying; Yang, Tian; et al.
Summary: Background: Effective adjuvant treatment after hepatectomy for hepatocellular carcinoma (HCC) is an important area of research. Radioactive iodine ( 131 I)-labelled metuximab is a radiolabelled monoclonal antibody against the CD147 (also known as basigin or HAb18G) antigen that is expressed in HCC. We aimed to examine the role of 131 I-metuximab as an adjuvant therapy after HCC resection. Methods: This randomised, controlled, multicentre, open-label, phase 2 trial was done at five medical centres in China. Patients aged 18–75 years who underwent curative-intent resection of histologically confirmed HCC expressing CD147 were randomly assigned (1:1) by a computer-generated random sequence, stratified by centre, to receive either adjuvant transarterial injection of one dose of 27·75 MBq/kg 131 I-metuximab 4–6 weeks after the hepatectomy (treatment group) or no adjuvant treatment (control group). Patients and physicians were not masked to the study groups. The primary outcome was 5-year recurrence-free survival (RFS) in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT00819650 . Findings: Between April 1, 2009, and Nov 30, 2012, 485 patients were screened for eligibility. 329 (68%) of these patients were excluded and 156 (32%) were randomly assigned to receive either 131 I-metuximab (n=78) or no adjuvant treatment (n=78). The median follow-up was 55·9 months (IQR 18·6–79·4). In the intention-to-treat population, the 5-year RFS was 43·4% (95% CI 33·6–55·9) in the 131 I-metuximab group and 21·7% (14·2–33·1) in the control group (hazard ratio 0·49 [95% CI 0·34–0·72]; Z=2·96, p=0·0031). 131 I-metuximab-associated adverse events occurred within the first 4 weeks in 34 (45%) of 76 patients, seven (21%) of whom had grade 3 or 4 adverse events. These adverse events were all resolved with appropriate treatment within 2 weeks of being identified. Interpretation: Adjuvant 131 I-metuximab treatment significantly improved the 5-year RFS of patients after hepatectomy for HCC tumours expressing CD147. This treatment was well tolerated by patients. Funding: State Key Project on Infectious Diseases of China.